Induction Of Protoplast Fusion Citrus In Vitro Germination In Medium By Addition Of Gibberellic Acid - Damarnegari, A A Ayu Laksmi; Astarini, Ida Ayu; Defiani, Made Ria; Kosmiatin, Mia (Metamorfosa: Journal of Biological Sciences, 2020)
Plant breeding is an effort to develop plants by manipulating the genetic system of plants to get new superior cultivars. Plant breeding often produces incompatible seeds, so a rescue process is needed to reduce the risk of embryo death.  The addition of gibberellic acid could break the seed dormancy for   seed that hard to germinate. The purpose of this study was to find out the best concentration of gibberellic acid for germination of citrus globular embryos from protoplast fusion.  Research was conducted at the Biology and Cell Biology Research Group In Vitro Culture Laboratory, Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development (BB BIOGEN), Agricultural Research and Development Agency, Ministry of Agriculture, Bogor.  The study used Completely Randomized Design (CRD) with concentration 0, 1, 2 and 3 ppm of gibberellic acid as treatment, each consists of 7 replicates.  This study used globular embryos measuring ± 3 mm of inbred FS 29 and FS 89 from protoplast fusion between Siam Simadu and Mandarin Satsuma citrus. Observations were made on the percentage of germinated embryos, time of germination, the number of the complete and incomplete shoot (abnormal, only part of the roots or buds that developed). Data were analyzed using Crosstab analysis test with IBM SPSS Statistics 22 software.  Result showed that addition of gibberellic acid induce faster germination time and increase seedling percentage.  The best germination medium for citrus FS 29 was VMW with 2 ppm and 3 ppm gibberellic acid with the seedling percentage around 85,7% in 7 days, while the best germination medium for citrus FS 89 was VMW with 1 ppm gibberellic acid with 100% seedling embryos in 8,5 days. VMW medium added with 1 ppm, 2 ppm and 3 ppm gibberellic acid for citrus FS29 and VMW medium added with 2 ppm and 3 ppm for citrus FS89 were good to get the complete sprouts with a succes rate of 100%.   Keyword : Citrus sp. gibberellic acid, incompatible, in vitro, embryo germination